HOW COUNSELING CAN INCREASE AWARENESS AND PERCEPTION OF VULNERABILITY TO EARLY DETECTION OF BREAST CANCER - Wulandari, Siswi; Viridula, Erike Yunicha; Novita, Kurnia; Anggraini, Yeni (Indonesian Journal of Health Science, 2024)
SADARI (Breast Self-Examination) is one of the early detection of breast cancer and a role in the discovery of early-stage breast cancer. Awareness about SADARI is an educational activity with the spread of messages to improve the implementation of SADARI and the perceived susceptibility of adolescents in the early detection of breast cancer. This research aims to determine the influence of counseling about awareness (breast self-examination) on implementing SADARI and perceived susceptibility to early detection of breast cancer in the Muhammadiyah Senior High School City of Kediri in 2022. Pre-experiment research with one group pre-test and post-test design. Population all student XI Muhammadiyah Senior High School with a sample size of 37 with a total sampling technique. The instrument is a questionnaire and statistics test by the Wilcoxon test. The results can be interpreted that before counseling on BSE, almost all respondents had less than 33 respondents (89.2%). After counseling, some respondents had the implementation of BSE in the medium category, namely 18 respondents (48.6%). Before counseling on BSE, almost all respondents had low perceived susceptibility, 25 respondents (67.5%). After counseling, most respondents had perceived susceptibility in the high category, namely 24 respondents (64.9%). The results by Wilcoxon test obtained Ï value = 0.000 < Î± = 0.05, which means there is an extension of awareness about SADARI on the implementation of SADARI and perceived susceptibility early detection of breast cancer. It is hoped that the youth will perform SADARI regularly and independently to detect early breast cancer